A Case of Narcolepsy with Strictly Unilateral Cataplexy - McCarty, David E. (American Academy of Sleep Medicine, 2010)
I report a case of a 50-year-old African American woman who presented for a sleep medicine evaluation complaining of excessive daytime sleepiness of greater than 10 years' duration. She reported falling asleep while driving, talking with friends, and eating. Her Epworth Sleepiness Scale score was 21/24. Her history was positive for the presence of sleep paralysis. She denied visual or auditory hallucinations in the peri-sleep period. CITATION: McCarty DE. A case of narcolepsy with strictly unilateral cataplexy. J Clin Sleep Med 2010;6(1):75-76.